Expression of the arsenite oxidation regulatory operon in Rhizobium sp. str. NT‐26 is under the control of two promoters that respond to different environmental cues. Issue 3 (17th December 2017) - Corsini, Paula M.; Walker, Kenneth T.; Santini, Joanne M.
Abstract: Rhizobium sp. str. NT‐26 is a Gram‐negative facultative chemolithoautotrophic arsenite oxidizer that has been used as a model organism to study various aspects of arsenite oxidation including the regulation of arsenite oxidation. The three regulatory genes, aioX, aioS, and aioR, are cotranscribed when NT‐26 was grown in the presence or absence of arsenite. The aioXSR operon is upregulated in stationary phase but not by the presence of arsenite in the growth medium. The two transcription start sites upstream of aioX were determined which led to the identification of two promoters, the housekeeping promoter RpoD and the growth‐phase‐dependent promoter RpoE2. Promoter– lacZ fusions confirmed their constitutive and stationary phase expressions. The involvement of the NT‐26 sigma factor RpoE2 in acting on the NT‐26 RpoE2 promoter was confirmed in vivo in Escherichia coli, which lacks a rpoE2 homolog, using a strain carrying both the promoter– lacZ fusion and the NT‐26 rpoE2 gene. An in silico approach was used to search for other RpoE2 promoters and AioR‐binding motifs and led to the identification of other genes that could be regulated by these proteins including those involved in quorum sensing, chemotaxis, and motility expanding the signaling networks important for the microbial metabolism of arsenite. Abstract : Regulation of the arsenite oxidase genes is controlled by the three component system AioXSR. The aioXSR operon is constitutively expressed and also upregulated in stationary phase, which is controlled by RpoD and RpoE2 promoters, respectively.